KEBIJAKAN KANADA MEMPERKUAT MILITERNYA DI SAMUDERA ARKTIK (2005-2013) - Arnold Stephan; Idjang Tjarsono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This study aims to analyze the reasons why Canada strengthen its military in the Arctic. In2005, under the leadership of Canadian prime minister, Paul Martin, Canada issuedInternational Policy Statement which emphasize the strengthening of Canadian military inthe Arctic. Furthermore, since 2006, under the new leadership of Canadian prime minister,Stephen Harper, Canada has announced its policy to strengthen the Canadian military in theArctic.This study uses the qualitative research methods with references taken from books, journals,papers and valid news from web. This study uses state-level analysis. The author uses neorealistperspective, and the theory of action-reaction model by Barry Buzan to analyze thequestion of the research.Since the end of the Cold War, Canadian military activity re-emerged in the Arctic region in2002, indicated by military operation and the presence of Canadian warships. In 2001,Russia claimed a region in the Arctic, which cause the territorial dispute with Canada.Russia also released the maritime doctrine in 2001, that emphasize the strengthening ofRussian naval power in the Arctic region. Under the leadership of Russian president VladimirPutin, and also to Dmitry Medvedev, Russian has strengthened its military in the Arctic bystrategic flights, balistic misille launching, military exercises, and with construction andmodernization of Russian Northern Fleet. Russian’s policy to strengthen its military in theArctic is a threat to Canada, so since 2005, Canadian Government has strengthened itsmilitary in the Arctic.Key Word: Arctic Ocean, Canadian military strengthening, territorial dispute, threat.